Budget-Based Compensation and Discretionary Spending. - Baber, William R. (The Accounting Review, 1985)
Abstract ABSTRACT: Budget-based compensation arrangements often are used in decentralized organizations to motivate manager decision-makers toward achieving organizational objectives. The use of budgets for this purpose can influence managers' decisions to make discretionary expenditures that yield future benefits. This study analyzes how budget-based compensation influences these decisions. The primary insight is that, if a lump-sum bonus is paid for meeting budgets, then managers prefer more discretionary expenditures when budgets are set at levels relatively difficult to achieve than when budgets are at levels easily attained.